Musyarakah Mutanaqisha Berbasis Lingkungan - Kevin Joan; Rahayu Atmana Putri; Ardy Nugraha; Bambang Catur Pambudi; Mukhsin Nur Firdaus (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
This paper attempts to offer a viable alternative model in developing coastal areas though utilization of waste in coastal areas that integrated with sharia micro-financing system, especially musyarakah mutanaqisha contract. The object of this study is the potential utilization of waste as an alternative to environment based financing with a musyarakah mutanaqisha financing system. This model is expected to provide an alternative solution for local government to meet their liquidity constraint in developing coastal areas. The paper is based on conceptual explorations of literature in the area of sharia micro-financing and waste problem. This paper is a conceptual paper, so it did not employ any empirical analysis. The findings of this paper provide musyarakah mutanaqisha financing model based on environment to support sustainable development in coastal areas.